Influence of Injection Energizing Durationand Injection Pressure for Palm Biodiesel in Common-rail Fuel Injection System - ศรีชัย, ประทาน (Princess of Naradhiwas University Journal, 2018)
This research presents fuel injection rate measurement with high pressure diesel injection system (Common Rail) at fuel injection pressure simulated real engine conditions. The investigation of relationship between fuel injection rate for diesel and palm biodiesel was studied by Zeuch’s method. This work aims to study influence of energizing duration and fuel injection pressure with results injection rate, energy contents, average speed and Reynolds number. The results showed that increase fuel injection timing results in increased fuel injection, but as the fuel injection pressure increases, the injection volume is greater than the fuel injection time. The lower energy content of biodiesel due to lower fuel heating value and injection quantity. The average fuel injection rate and the Reynolds number of palm biodiesel are less than those of diesel due to increased viscosity of palm biodiesel. The fuel flow resistance and consequently the effect of fuel dispersion decreases. The way to reduce the amount of biodiesel fuel has done by increasing the fuel injection pressure to reduce the fuel injection resistance.